Photoinduced Heterogeneous C−H Arylation by a Reusable Hybrid Copper Catalyst - Choi, Isaac (Chemistry, 2020)
Heterogeneous copper catalysis enabled photoinduced C−H arylations under exceedingly mild conditions at room temperature. The versatile hybrid copper catalyst provided step‐economical access to arylated heteroarenes, terpenes and alkaloid natural products with various aryl halides. The hybrid copper catalyst could be reused without significant loss of catalytic efficacy. Detailed studies in terms of TEM, HRTEM and XPS analysis of the hybrid copper catalyst, among others, supported its outstanding stability and reusability.